Microstructure analysis of high density WC-Co composite prepared by one step selective laser melting. (November 2019) - Chen, Jian; Huang, Miaojun; Fang, Zak Zhigang; Koopman, Mark; Liu, Wei; Deng, Xin; Zhao, Zhe; Chen, Shaohua; Wu, Shanghua; Liu, Jianye; Qi, Wenjun; Wang, Zhongping
Abstract: WC-Co composite, also well known as cemented carbide, is one of the most challenging materials for one step additive manufacture process, such as selective laser melting (SLM). Up until now, defect free cemented carbide has never been successfully synthesized yet using one-step SLM. In this study, the critical effect of the morphology of feedstock carbide granules on the microstructure was initially investigated for SLM processed carbides. Crack free WC-20Co cemented carbide with high density has been successfully synthesized using one-step SLM without further heat treatment. The density is significantly high for SLM processed carbides although still unsatisfactory yet compared to conventional liquid phase sintered carbides. Spherical granules are more favorable than non-spherical granules in obtaining a higher final density. The SLM process results in inhomogeneous and rapid WC grain growth, which is attributed to the non-uniform temperature distribution and varying amount of time experienced by the material in the liquid state during the SLM process. Highlights: Cemented carbide is one of the most challenging materials for SLM process. In this study, we developed a unique and optimized SLM processing to make high density WC-Co carbide. The research highlights include: Selective laser melting (SLM) was used to make bulk cemented carbide in this study. A significantly high relative density of more than 96% was achieved for WC-20Co cemented carbide by one step SLM processing. It was found that spherical pellets are significantly more favorable than non-spherical pellets in obtaining a higher final density. SLM processing introduced significant, rapid, and non-uniform WC grain growth, resulting in a unique lamellar microstructure.